NOSOCOMIAL URINARY TRACT INFECTIONS, AND THEIR SUSCEPTIBILITY TO ANTIMICROBIAL AGENTS IN SPINAL CORD INJURY PATIENTS AT A REHABILITATION SETTING - Syed Ali Raza Ali Shah (Army Medical College Rawalpindi, 2021)
Objective: To identify frequency of nosocomial urinary tract infections along with their antibiotic susceptibility in spinal cord injury patients.